Malignant Transformation of a Borderline Ovarian Tumor With Pulmonary and Pleural Metastases After Years of Latency: A Case Report and Literature Review - Ma, Jiang-wei; Miao, Yuan; Liang, Chao-nan; Wang, Ning; Jiang, Bin; Wang, Qiu-yue; Kang, Jian; Hou, Gang; Yin, Yan (Frontiers in Medicine, 2020)
Borderline ovarian tumor (BOT) refers to a distinct tumor of the ovary of epithelial origin and typically has a favorable prognosis. However, these tumors are not exempt from risks of recurrence and malignant transformation, which can arise from the remaining ovarian tissue, peritoneal implants or distant localization. Here, we report a case of a mucinous BOT with multiple pulmonary cystic nodules without evidence of pulmonary metastasis even after two fine needle biopsies. Cytoreductive surgery was performed, and no evidence of peritoneal implants or invasion to adjacent organs found. At the end of the seven-year monitored follow-up after surgery, the pulmonary lesions were found to be increased in size. The transbronchial lung biopsy and pleural biopsy confirmed transformation into malignant mucinous adenocarcinoma with pleural metastasis. In the current case, we observed potential pulmonary metastasis of the BOT with malignant transformation and a latency as long as seven years, which reminds us that multiple pulmonary cystic changes in patients with BOTs should be screened carefully to evaluate the pulmonary involvement of BOTs and potentially false-negative results after fine needle biopsy. Thus, a thorough check-up for complete staging of the disease and a close long-term follow-up to monitor potential recurrence and malignant transformation are advised.